RESULTS OF GRAFTING PISTACHIO ECOTYPES COLLECTED FROM VARIOUS REGIONS OF UZBEKISTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Central Asia is considered the homeland of the pistachio. This tree not only serves important forest reclamation functions but also produces valuable nuts. The demand for pistachios in the global market is considered high. Countries that cultivate pistachios are conducting a series of scientific studies aimed at increasing the yield of pistachio plantations. These studies mainly focus on establishing pistachio plantations, reducing the period before cultivated pistachio orchards begin to bear fruit, increasing productivity, and improving the quality of pistachio nuts.
Keywords: pistachio, mountains and foothills, forest reclamation, rainfed, arid, nut-bearing, grafting, rootstock, scion, ecotype, genotype, mother tree